Ischemic colitis and pneumatosis intestinalis in a patient with COVID-19: a case report - Vélez Páez, Jorge Luis (2021)
The severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is the virus causing the ongoing pandemic. In general, patients infected with SARS-CoV-2 develop respiratory diseases. The first symptoms are fever, cough and dyspnea that rapidly progress to pneumonia. Additionally, extrapulmonary manifestations, such as those in the gastrointestinal system, have been reported. It has been described that the angiotensin-converting enzyme 2 (ACE2) receptor and the transmembrane serine protease 2(TMPRSS2) for S protein priming favor SARS-CoV-2 entry into the cells. These proteins are expressed in alveolar type II cells as well as in ileum and colon enterocytes, thus detecting the virus in the digestive tract. We present the case of a patient with COVID-19 pneumonia and gastrointestinal findings such as pneumatosis intestinalis and ischemic colitis.